Communication—On the Lack of Correlation between the Voltammetric Redox Couple and ORR Activity of Fe-N-C Catalysts. Issue 13 (28th September 2020) - Elvington, Mark C.; Chung, Hoon T.; Lin, Ling; Yin, Xi; Ganesan, Prabhu; Zelenay, Piotr; Colón-Mercado, Héctor R.
Abstract : Platinum group metal-free catalysts for polymer electrolyte fuel cells are analyzed in different electrolytes (H2 SO4 and HClO4 ) and at different pH values to gain insight into the oxygen reduction reaction (ORR) mechanism. Two Fe-N-C type catalysts showing a reversible voltammetric redox couple around 0.77 V vs RHE in HClO4 electrolyte are investigated. A notable cathodic shift of the redox couple to 0.62 V is observed in H2 SO4 and is assigned to bisulfate adsorption. Concurrently, the ORR activity of the catalysts is unaffected, suggesting an independent nature of the reductive mechanism with the redox peak species.